Examining the Criticality of Definition of Micro, Small and Medium Enterprises (MSMEs): A Review with Special Reference to India and Its Policy Implications - Nidhi Gautam; Nishant Tiwary (International Journal of Small and Medium Enterprises and Business Sustainability, 2020)
Amidst the adverse impact caused by COVID-19 on the industries, Micro, Small and Medium Enterprises (MSMEs) are worst hit. As a relief package to the sector, government has recently announced new definition for MSMEs. The government has redefined MSMEs on the basis of investment and turnover. Present paper attempts to critically review the secondary literature of defining parameters of MSMEs across the countries as well as in Indian context is done. The paper discusses in detail the issue with the definition of MSMEs at global and national level and the changed perspectives for MSMEs with the new definition of MSMEs.